The Avoidance Practice and Its Association with Self-Efficacy, Knowledge and Attitude among Mothers with Children under 6 Years Old on Environmental Tobacco Smoke Exposure to Their Children in Selangor - Abdul Halim, Nursakinahsharifah; Md Yasin, Mazapuspavina; Miptah, Hayatul Najaa; Ismail, Nurhuda (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Environmental tobacco smoke (ETS) poses significant health risks globally, particularly for children. This study aimed to determine levels of self-efficacy, knowledge, attitude, and avoidance practices regarding ETS exposure among mothers with children under six and identify factors associated with avoidance practices. MATERIALS AND METHODS: A cross-sectional study was conducted using the validated Malay SE-KAP-ETS questionnaire among 321 mothers. Higher scores indicated better self-efficacy, knowledge, attitude, and avoidance practices. Multiple linear regression (MLR) analysis was performed to determine associations. RESULTS: Participants had a mean age of 33.4(±5.57), and 67.9% had tertiary education. Mean scores were: self-efficacy 36.41(±9.7), knowledge 38.26(±3.76), attitude 48.58(±3.75), and avoidance practices 28.33(±3.27). MLR revealed that no smokers at home [B=0.700, 95%CI: 0.304, 1.462; p=0.003], higher self-efficacy [B=0.058, 95% CI: 0.028, 0.088; p<0.001], and positive attitudes [B=0.414, 95%CI: 0.336, 0.491; p<0.001] were positively associated with avoidance practices. Conversely, primary and secondary education [B=-0.750, 95% CI: -1.449, -0.051; p<0.035] and self-employment [B=-1.517, 95%CI: -2.584, -0.450; p=0.005] were negative predictors. CONCLUSION: Findings indicate that although ETS knowledge is high among mothers of young children in Selangor, it does not predict avoidance practices. Instead; self-efficacy, attitude, and smoke-free homes are critical determinants, underscoring the need for empowerment-focused interventions, particularly for mothers with primary and secondary education.